Les terrains de football à Yaoundé : usages et conflits d’accès aux espaces publics - Luc-Roger Mballa Bekolo; Antoine Marsac; Patrick Bouchet (EchoGéo)
In Yaoundé, football fields, spaces developed and open to play, are limited in number. Faced with high demand, their access remains problematic for residents. Our sociological study focuses on the observation of users of these stadiums and their views on access to the sites at the scale of the 6th arrondissement of the Cameroonian capital. If this municipality officially manages occupancy fees and schedules, uses diverge, generating conflicts. We reproduce its complexity in the light of the social transactions at the work at the neighbourhood level. Despite the establishment of management committees, tensions are rising particular among young people. This context leads to discrimination between the public. In the end, this situation proves to be unfavorable to leisure practitioners.